Allozyme and morphological identification of Anisakis, Contracaecum and Pseudoterranova from Japanese waters (Nematoda, Ascaridoidea) - MATTIUCCI, Simonetta; PAGGI, Lia; NASCETTI, Giuseppe; CIANCHI, Maria Rossella; BULLINI, Luciano; Hajime Ishikura; Kokichi Kikuchi; Noriyuki Sato (KLUWER ACADEMIC PUBL, 1998)
Allozyme markers were used to identify anisakid nematodes from marine Japanese waters, morphologically assigned to three species complexes: Anisakis simplex (s. l.), Contracaecum osculatum (s. l.) and Pseudoterranova decipiens (s. l.). Samples assigned to A. simplex (s. l.) were found to correspond genetically to A. simplex (sensu stricro), those of C. osculatum (s. l.) to C. osculatum A. No morphological characters are yet available to distinguish sibling species of these two complexes. As to the P. decipiens complex, two distinct species were detected: the first corresponded to P. decipiens C, previously recovered in the northern Atlantic, the second to P. decipiens D from Japan. The two species are genetically well differentiated, with five of the 19 loci tested showing distinct fixed alleles. Their reproductive isolation was proved by the lack of hybrids or recombinants in sympatric samples recovered from the same definitive host, Erignathus barbatus. P. decipiens D was found to correspond morphologically to Porrocaecum azarasi, previously considered a synonym of P. decipiens. Accordingly, the name Pseudoterranova azarasi (Yamaguti & Arima, 1942) n. comb. is proposed for P. decipiens D. Similarly, P, decipiens C fits in general morphology, type-locality and host with Ascaris bulbosa, also previously considered a synonym of P, decipiens. The name Pseudoterranova bulbosa (Cobb, 1888) n. comb. is proposed for P. decipiens C.